2018
DOI: 10.1016/j.jaad.2017.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide use and risk of nonmelanoma skin cancer: A nationwide case-control study from Denmark

Abstract: Hydrochlorothiazide use is associated with a substantially increased risk of NMSC, especially SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
229
8
11

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 239 publications
(265 citation statements)
references
References 26 publications
17
229
8
11
Order By: Relevance
“…14,15 However, whether photosensitizing AD use affects cSCC risk is unclear. Previous observational studies have produced conflicting results, [16][17][18][19][20][21][22][23][24] and limitations have included small sample sizes, 22 reliance on self-reported medication history, 23 confounding by indication, incomplete capture of cases 19,20,24 and lack of pathological verification. 19,20,22,24 In this study, we examined the association between AD use and cSCC risk among 28 357 non-Hispanic white (NHW) patients with hypertension in a closed healthcare system in northern California with integrated electronic pharmacy records and pathologically verified cSCC cases.…”
mentioning
confidence: 99%
“…14,15 However, whether photosensitizing AD use affects cSCC risk is unclear. Previous observational studies have produced conflicting results, [16][17][18][19][20][21][22][23][24] and limitations have included small sample sizes, 22 reliance on self-reported medication history, 23 confounding by indication, incomplete capture of cases 19,20,24 and lack of pathological verification. 19,20,22,24 In this study, we examined the association between AD use and cSCC risk among 28 357 non-Hispanic white (NHW) patients with hypertension in a closed healthcare system in northern California with integrated electronic pharmacy records and pathologically verified cSCC cases.…”
mentioning
confidence: 99%
“…The first matched 633 patients with squamous cell carcinoma (SCC) of the lip with 63 067 population controls 2. The second was a study of 71 533 patients with basal cell carcinoma (BCC) and 8629 case patients with SCC who were matched with 1 430 883 and 172 462 population controls, respectively 3.…”
Section: Overviewmentioning
confidence: 99%
“…In an exploration of linked data from the Danish Cancer and Prescription Registries, an association was found between receipt of an amiloride/hydrochlorothiazide combination product and the occurrence of lip cancer . Using the same data source, the researchers next showed that exposure to hydrochlorothiazide in drug combinations other than amiloride/hydrochlorothiazide was also associated with an elevated risk for lip cancer as well as nonmelanoma skin cancers . The hypothesis generated and refined in the Danish data was that the use of hydrochlorothiazide predisposes patients to skin cancer.…”
Section: Investigation Of Biologically Based “Orthogonal” Hypothesesmentioning
confidence: 99%